Svatantratāndolanam : Bhāritīyakāṅgresasyetihāsaḥ - Pāṇḍeya, Dineśa Prasāda (Subodha Granthamālā Kāryālaya, 1975)
On the history of the Indian freedom movement with special reference to the activities of the Indian National Congress.